STUDY ON NATURAL DURABILITY OF Schizostachyum brachycladum THROUGH SHORT TERM GRAVE YARD TEST - Siti Katijah Ismail (2013)
The study was determined the physical and durability properties of untreated bamboo Schizostachyum brachycladum was evaluated through the short-term grave yard test. The results showed that the moisture content was decreasing due to the increasing of i age group which is in range 49.29% to 80.57%. The basic density was increase due to increasing of age group which is in range 0.61 to 0.81. For the durability properties, pest caused weight loss to Schizostachyum brachycladum in the grave yard test results that shown weight loss of Schizostachyum brachycladum have the relationship with the moisture content and basic density based on their age group. The weight loss of Schizostachyum brachycladum in term of percentages after three month in grave yard test was from 18.29% to 36.63%. Statistical analysis indicated significant differences between age group and among internodes proposition both for physical and durability properties. Key words: Schizostachyum brachycladum, Physical properties, Durability Properties, Grave yard test